P64 Hybrid high fidelity military simulation. (5th November 2017) - Fadden, SJ; Jones, CP; Round, JA; Mercer, SJ
Abstract : Context: The return to contingency operations has presented the Defence Medical Services (DMS) with new challenges for training and maintenance of non-technical and technical trauma skills. 1 The Military Operational Surgical Training course (MOST), 2 delivered at the Royal College of Surgeons, London, has changed significantly to address these challenges. Designed for multidisciplinary deployable trauma teams, the MOST course includes lectures, workshops, practical skill stations, cadaveric surgical procedure sessions and simulation training. Standard wireless simulation mannequins fail to deliver the surgical fidelity required to allow formal evaluation of non-technical and technical skills for Damage Control Resuscitation and Surgery (DCR and DCS). We present the outcomes of an evolved simulation activity that supports whole team assessment. Methodology: During MOST candidates undertake several sessions of high fidelity fully immersive simulation training, conducted in a simulation suite which has been set up as a military medical resus bay. On the final day, when each simulation progresses to reach a standardised "command huddle", to establish a formal plan for surgery (with or without imaging), the scenario is paused. The team is then taken to a mock theatre in a wet laboratory, presented with a fresh frozen human cadaveric patient, and asked to continue as planned. Real-time monitoring is provided via a SimMon app, and investigation results via the faculty, whilst surgical interventions are performed on the cadaver. This hybrid simulation facilitates the entire team's engagement in the execution of DCR and DCS. On completion of each scenario, a video-assisted collaborative debrief is guided by subject-matter experts. Outcomes: Evaluation of the novel hybrid simulation training was discerned from candidate feedback, collected since the inauguration of the course in 2010. Feedback has been positive, indicating that candidates perceive an improvement of their technical and non-technical skills, particularly in terms of equipment orientation, performance of anaesthetic and surgical procedures, decision-making, team work and crew resource management. Many candidates remarked on the "value" of enhanced "realism" for the development of their "understanding" and "confidence" in managing future real-life scenarios. One candidate went as far as to testify that simulation training "does not get any better than this". Conclusion: Hybrid simulation is a stimulating and effective novel training tool. Limitations to widespread implementation of this training include cost and resource implications. Substituting human for porcine cadavers would reduce the financial burden. The full benefit of hybrid simulation training, in both military and civilian settings, is yet to be exploited. References: . Mercer SJ, Khan MA, Scott T, Matthews JJ, Henning D, Stapley S. Human factors in contingency operations. JRAMC April 2017 ;163(2):78–83. . Mercer SJ, Jones C, Round J, Parkhouse D. Military Anaesthesia in contingencies: What skill sets are required and how will we prepare our trainees? JRAMC 2017. doi:10.1136/jramc-2016-000722